Antibodies against EGF-like domains in Ixodes scapularis BM86 orthologs impact tick feeding and survival of Borrelia burgdorferi - Juraj Koči (Nature Portfolio, 2021)
Abstract Ixodes scapularis ticks transmit multiple pathogens, including Borrelia burgdorferi sensu stricto, and encode many proteins harboring epidermal growth factor (EGF)-like domains. We show that I. scapularis produces multiple orthologs for Bm86, a widely studied tick gut protein considered as a target of an anti-tick vaccine, herein termed as Is86. We show that Is86 antigens feature at least three identifiable regions harboring EGF-like domains (termed as EGF-1, EGF-2, and EGF-3) and are differentially upregulated during B. burgdorferi infection. Although the RNA interference-mediated knockdown of Is86 genes did not show any influences on tick engorgement or B. burgdorferi sensu stricto persistence, the immunization of murine hosts with specific recombinant EGF antigens marginally reduced spirochete loads in the skin, in addition to affecting tick blood meal engorgement and molting. However, given the borderline impact of EGF immunization on tick engorgement and pathogen survival in the vector, it is unlikely that these antigens, at least in their current forms, could be developed as potential vaccines. Further investigations of the biological significance of Is86 (and other tick antigens) would enrich our knowledge of the intricate biology of ticks, including their interactions with resident pathogens, and contribute to the development of anti-tick measures to combat tick-borne illnesses.